A new record of the genus Limnocletodes Borutzky, 1926 (Cletodidae: Harpacticoida) with redescription of three species from Vietnam - Luong, Tran Duc; Hai, Ho Thanh; Minh, Le Danh (Academia Journal of Biology, 2013)
The genus Limnocletodes Borutzky, 1926 comprises six species in the world, such as Limnocletodes behningi Borutzky, 1926; L. secundus Sewell, 1934; L. angustodes Shen & Tai, 1963; L. oblongatus Shen & Tai, 1964; L. mucronatus Gee, 1998 and L. wellsi Gee, 1998. Three newly recorded species of this genus collected from inland fresh waters of Vietnam are L. behningi, L. angustodes and L. oblongatus. The redescription of these species are provided and illustrated with the systematic discussion. The specimens of L. angustodes from Vietnam have similar features with the original description by Shen & Tai, 1963; Kikuchi et al. (1993)'s redescription from China and the detailed redescription of Lee & Chang (2007) from Korea. Some little variability showed the tiny inner seta on distal edge of A2 Enp; length/width ratio of furca larger (1.2-1.5 times vs. 1.1-1.3 times) and inner caudal seta longer than outer caudal seta. The specimens of L. oblongatus from Vietnam fitted well with the original description from Chinese specimens, except Exp of P5 in female smaller and not reaching to apex of Enp. Furthermore, the spine of Exp-1 of P4 slightly larger and the inner seta of P4 Exp-2 is normal development, plumose form (instead of reduced to setuliform). The L. behningi in Vietnam with P4 Enp equal in length to Exp-1 (same as the redescription of Shen & Tai, 1963) but P3 Enp is much longer than Exp-1 (equal in length according to Lang, 1948; Shen & Tai, 1963). Vietnamese specimens come close to the opinion of Gee (1998) about the length of Enp-2 in relation to Exp-1 in female P2 and P3 (about 1.03 and 1.05 times in length respectively). Furthermore, Vietnamese specimens are distinguished from L. behningi and other species in the genus by the shape and length of P1 Enp-1, it is elongate and longer than both Enp-2 and Exp-1. However, according to the opinion of Wells (1971) and Lee & Chang (2007), the character of relative length ratio between endopod (or Enp-2) and Exp-1 in P2-P4 (probably P1 too) is not consistent and rather variable. So, we think that the differences of P1 in female of Vietnamese specimens are only new variant type of L. behningi.